Conflitos e contradições no município de Ferros: o mineroduto Manabi - Bruno von Sperling; Profa. Dra. Doralice Pereira (Confins)
With the Brazilian government's re-primarization of the economy and the interests of the capitalists, including the exponential growth of the price of iron ore in the global market, the River Santo Antônio watershed became the target of mega-mining projects. One of these projects belongs to the Manabi company, which, since 2012, intends to extract ore in the region and transport it through a pipeline, to a port in Espírito Santo state’s coast, from where it would be exported. The focus of the present article is to analyze the hierarchical social relations in some communities in Ferros county, which turned to get more complex since Manabi announced they intentions to build its pipeline there.